True Riches; Or, Wealth Without Wings - Arthur, T. S. (Timothy Shay), 1809-1885 (Salt Lake City, UT : Project Gutenberg, 2005)
"True Riches; Or, Wealth Without Wings" by T. S. Arthur is a novel written in the mid-19th century. The story explores themes of true wealth versus material riches through the lives of its central characters, such as Edward Claire and his wife Edith, as well as the morally dubious merchant Leonard Jasper. The narrative delves into the temptations faced by Edward as he navigates a world where dishonest practices in business can lead to significant gain, juxtaposing his ambitions with the loving and principled values upheld by Edith. At the start of the novel, we are introduced to Edward Claire, who is employed by the unscrupulous Leonard Jasper. After a notably profitable day for Jasper, Edward struggles with the ethical implications of their business practices while witnessing the passing of a family, which complicates his moral standing. The opening chapters also depict a touching family dynamic between Edward, Edith, and their young child, alongside the tragic fate of the orphan Fanny Elder. As the couple grapples with the suggestion of taking Fanny into their home, the tension between material ambitions and moral integrity unfolds, revealing the inner conflict within Edward and the virtues his wife embodies. The narrative sets the stage for a deeper examination of what constitutes true wealth$1 (Ban exploration that challenges societal values of the time. (This is an automatically generated summary.)s
Release date is 2005-03-16
Produced by Internet Archive Children's Library, Joshua Hutchinson, S.R.Ellison and the Online Distributed Proofreading Team
Keywords: Orphans -- Fiction; Honesty -- Fiction; Christian life -- Fiction; Adopted children -- Fiction; Families -- Fiction